2011
DOI: 10.1016/j.ajpath.2011.08.006
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin and K-RAS Synergize to Form Primitive Renal Epithelial Tumors with Features of Epithelial Wilms' Tumors

Abstract: Wilms' tumor (WT) is the most common childhood renal cancer. Although mutations in known tumorassociated genes (WT1, WTX , and CATNB) occur only in a third of tumors, many tumors show evidence of activated ␤-catenin-dependent Wnt signaling, but the molecular mechanism by which this occurs is unknown. A key obstacle to understanding the pathogenesis of WT is the paucity of mouse models that recapitulate its features in humans. Herein, we describe a transgenic mouse model of primitive renal epithelial neoplasms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 66 publications
3
34
0
Order By: Relevance
“…25 This study, coupled with our K-Ras depletion results, suggests that while mutant K-Ras and other genetic aberrations are required for increasing the levels of survivin, depletion of only K-Ras is able to decrease survivin. Therefore, K-Ras is necessary for the maintenance of survivin but not sufficient to increase survivin levels.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…25 This study, coupled with our K-Ras depletion results, suggests that while mutant K-Ras and other genetic aberrations are required for increasing the levels of survivin, depletion of only K-Ras is able to decrease survivin. Therefore, K-Ras is necessary for the maintenance of survivin but not sufficient to increase survivin levels.…”
Section: Discussionsupporting
confidence: 63%
“…Consistent with our results, expression of mutant K-Ras in mouse kidneys in the Wilms tumor mouse model was not able to induce survivin. 25 Interestingly, in this model, expression of both mutant K-Ras and β-catenine levels was demonstrated in cancer cell lines from different tissue of origin. Therefore, our results suggest that the requirement of K-Ras expression for the maintenance of aberrantly high levels of survivin in human cancer cells depends on the mutation status of K-Ras but is not tissue-specific.…”
Section: Discussionmentioning
confidence: 86%
“…Primitive tubules are normally seen in the developing kidney or in pediatric diseases such as Wilms' tumors. There is evidence for the activation of ␤-catenin/Wnt signaling in Wilms' tumors (8), and it has been suggested that ␤-catenin/Wnt signaling is activated in PKD as well (22,32), although this is debatable, as it does not appear to be true in all models (26). In our studies we found increased EMT and Wnt signaling in hyperglycemic cilia Ϫ kidneys.…”
Section: Discussionmentioning
confidence: 43%
“…All mice were bred and housed under an Institutional Animal Care and Use Committee approved protocol. Mice were crossed to obtain mice with genotypes γGT-Cre/Catnb +/lox(ex3) (referred to as Catnb Δex3 ), γGT-Cre/Kras +/G12D (referred to as Kras G12D ), γGT-Cre/Kras +/G12D /Catnb +/lox(ex3) (referred to as Kras G12D /Catnb Δex3 ) and litter-mate controls as previously described 11 . For the microarray experiment, mice were sacrificed at age 15–20 weeks and the kidneys flash frozen in liquid nitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…We showed that constitutive restricted activation of the canonical Wnt/β-catenin pathway in murine renal tubular epithelial cells late in renal development is sufficient to induce small tumors with features of human WT 11 . Metastatic disease progression required the simultaneous addition of an activating mutation of the G-coupled protein/oncogene K-ras .…”
Section: Introductionmentioning
confidence: 95%